Kinetics of the charge ordering in magnetite below the Verwey temperature - Gooth, Johannes; Boehnert, Tim; Gluschke, Jan G.; Hamdou, Bacel; Barth, Sven; Goerlitz, Detlef; Zierold, Robert; Nielsch, Kornelius (Journal of Physics: Condensed Matter, 2014)
In this work the kinetics of the charge ordering in magnetite (Fe3O4) below the Verwey transition temperature TV is investigated in time and energy domain. After excitation by a one-second voltage pulse to destruct the charge-ordered state below TV, an alternating current (AC) is used to perturb its recovery process. Upon warming up to above a temperature Tr(< TV) the charge order recovers despite the ac perturbation, because the temperature-dependent relaxation time becomes shorter than the polarity change of the ac. From the frequency dependence of Tr(f), an activation energy of ΔE = 126 meV is extracted. Below Tr the real part of the ac conductance Greal follows the relation Greal ∼ fα with α = 0.98 ± 0.18, suggesting that the charge reordering is driven by correlated hopping transport. The relaxation time τ = 1/f(Tr) of the charge-ordered state is determined for temperatures between 70 and 98 K and is extrapolated to τ(TV) = 1.6 ms, continuously slowing down its dynamics as the temperature is decreased.
CRIS-Team Scopus Importer:2023-03-20
Keywords: charge order; correlated transport; electric field; magnetite; phase transition; trimeron; verwey transition